2013
DOI: 10.3389/fnhum.2013.00599
|View full text |Cite
|
Sign up to set email alerts
|

Multisite functional connectivity MRI classification of autism: ABIDE results

Abstract: Background: Systematic differences in functional connectivity MRI metrics have been consistently observed in autism, with predominantly decreased cortico-cortical connectivity. Previous attempts at single subject classification in high-functioning autism using whole brain point-to-point functional connectivity have yielded about 80% accurate classification of autism vs. control subjects across a wide age range. We attempted to replicate the method and results using the Autism Brain Imaging Data Exchange (ABIDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
267
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(285 citation statements)
references
References 56 publications
(85 reference statements)
12
267
5
1
Order By: Relevance
“…Indeed, previous studies using the ABIDE data have shown that acquisition site has significant effects on basic image properties (Nielsen et al, 2013;Castrillon et al, 2014). This further exacerbates the problem of identification of core neuroanatomical abnormalities in this extremely heterogeneous data.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, previous studies using the ABIDE data have shown that acquisition site has significant effects on basic image properties (Nielsen et al, 2013;Castrillon et al, 2014). This further exacerbates the problem of identification of core neuroanatomical abnormalities in this extremely heterogeneous data.…”
Section: Introductionmentioning
confidence: 88%
“…The great majority of ASD studies have focused on identifying group differences between typically developing individuals and those with ASD, or conversely, training classifiers to distinguish between these groups (Ecker et al, 2010;Nielsen et al, 2013;Wang et al, 2015). But, perhaps the largest source of heterogeneity is associated with the severity of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic Observation Schedule (21)(22)(23), the Autism Diagnostic Interview-Revised (20), and the Social Responsiveness Scale (SRS) (19,22,24). As such, brain measures may explain additional variance in behavioral outcomes.…”
mentioning
confidence: 99%
“…Functional connectivity strength in individuals with ASD has been found to predict an ASD diagnosis (19)(20)(21) and to correlate with many aspects of cognition and behavior that also predict outcome, including IQ (21,22), and ASD symptomatology using the Autism Significance Few individuals diagnosed with autism spectrum disorder (ASD) go on to achieve high levels of independence or what are considered "very good" outcomes. As such, there is a need to identify predictors of outcomes to improve treatment and services for these individuals.…”
mentioning
confidence: 99%
“…Pattern classification methods demonstrate a high predictive ability for the detection of ASD and have been performed across a variety of imaging modalities. These include structural MRI [11][12][13], intrinsic functional connectivity MRI (fcMRI) [14][15][16], diffusion tensor imaging (DTI) [17,18] and electroencephalography (EEG) [19,20]. Reported ASD abnormalities have been identified in the cerebellum [21] and cerebellar vermis [22], anterior cingulate gyrus [23], amygdala [24][25][26], hippocampus [24,27,28], and areas of the frontal [29][30][31], temporal [29,32] parietal lobes [30], caudate and putamen [29,33].…”
Section: Introductionmentioning
confidence: 99%